Infantile Colic in Infants Aged One-Six Months and the Practices of Mothers for Colic - Nurdan Akçay Didişen; Betül Yavuz; Gülçin Özalp Gerçeker; Tuğba Albayrak; Meryem Atak; Didar Zümrüt Başbakkal (Galenos Yayinevi, 2020)
Aim:The aims of this study were to explore the infantile colic in infants from 1-6 months of age, and the mother's practices to eliminate colic and the relationships between infantile colic scores and sample characteristics.Materials and Methods:This descriptive study included 232 mothers of infants who were admitted to the hospital for child monitoring at two university hospitals in the Aegean region. Information on demographics, colic characteristics, and practices of mothers to eliminate colic was collected.Results:According to reports of the mothers, 67.2% of the infants had colic, and 28.5% of the infants met all of the Wessel criteria. The average scale score of infantile colic was 65.2±12.6. To eliminate the colic, 67.6% of the mothers held their infants on their lap, 68.7% rocked them, 63.2% changed the position of their infants, 57.4% massaged the infants' bellies, and 37.1% stated that they used a warm application.Conclusion:One out of every three-four babies in the study met the diagnosis of infantile colic according to Wessel criteria's. The average score obtained from the infantile colic scale is quite high. Mothers usually use behavioral methods to prevent and reduce colic symptoms, they also use pharmacological and traditional methods in this study.